The Influence of Online Customer Reviews, Prices, and Sales Promotions on Buying Interests in the Tokopedia Marketplace - Hartawati; Wiraatmaja, Jessica; Jeffrie; Nurbasari, Anny (The Journal of Management, Digital Business, and Entrepreneurship, 2023)
In early 2020, Indonesia was affected by the COVID-19 Pandemic; this increased the habits of Indonesian people shopping online through marketplaces such as Tokopedia, Shopee, Lazada and so on. Marketplaces are competing to provide attractive offers during the Pandemic. The value of shopping transactions at Shopee is 40%, Tokopedia is 30%, and Lazada is 16%. It is known that Shopee is the most popular marketplace for Indonesians at the peak of Harbolnas 2021 compared to Tokopedia. This study aims to determine the effect of online customer reviews, prices and sales promotions on purchase intention at Tokopedia. The population of this research is Tokopedia users in Indonesia, with a total sample of 174 respondents. The method used is quantitative, and the data is processed using SmartPLS 3.2.9 software. The results of this study indicate that the OCR variable, price and sales promotion have a positive effect on purchase intention. The independent variable that has the most dominant influence on the dependent variable of purchase intention is the online customer review factor.